The Historical Slave Trade and Firm Access to Finance in Africa - Pierce, Lamar; Snyder, Jason A. (Review of Financial Studies, 2018)
Access to finance helps explain the link between the historical African slave trade and current gross domestic product. We first present mistrust, weakened institutions, and ethnic fractionalization as plausible historical channels linking the slave trade to modern finance and development. We then show (i) the slave trade is consistently linked to reduced access to the formal and trade credit needed by modern firms, (ii) this shortage particularly reduces capital investment in smaller firms not in business groups, and (iii) the slave trade cannot explain most other business obstacles, suggesting that long-term societal shocks are exceptionally important for finance. Received December 16, 2014; editorial decision June 29, 2017 by Editor Philip Strahan.